Epistimologi Filsafat Kewirausahaan: Membaca Konsep Entrepreneurship Musa Asy’arie - Sochimin Sochimin (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
Musa Asy'arie is a professor of philosophy, but on the other hand has expertise in the field of entrepreneurship. This can be seen from both his scientific works and his involvement in practical economic activities. This very comprehensive mastery of the two scientific domains in Musa Asy'arie has its own charm to be studied and explored further, thus giving rise to a philosophical scientific paradigm that integrates with empirical applications in the realm of entrepreneurship. This research shows the critical thinking of a Musa Asy'arie towards the political policies of the leaders of the Indonesian nation from time to time, especially those related to the pattern of forming the nation's mental attitude, seen from a philosophical perspective